558 Fertility-sparing treatment for early stage cervical cancer: a single center experience with conization and nodal evaluation. (4th December 2020) - Martinelli, Fabio; Ditto, Antonino; Filippi, Francesca; Bogani, Giorgio; Roberti Maggiore, Umberto Leone; Evangelista, Mariateresa; Signorelli, Mauro; Chiappa, Valentina; Lopez, Salvatore; Somigliana, Edgardo; Raspagliesi, Francesco
Abstract : Introduction/Background: To evaluate oncological and obstetrical outcomes of early stage cervical cancer patients who attempted a conservative management to retain their childbearing potential. Methodology: Data of women (aged <40 years) who attempted a fertility sparing treatment for FIGO stage IA1-LVSI+, IB1 and IB2 cervical cancer were prospectively collected. All patients underwent cervical conization/s and laparoscopic nodal evaluation (pelvic lymphadenectomy/sentinel node mapping). Oncological and obstetrical outcomes were assessed. Results: Overall, 44 patients met the inclusion criteria. Forty-one (93.2%) women were nulliparous. There were: 3 (6.8%) IA1-LVSI+; 11 (25%) IA2; 25 (56.8%) IB1; 5 (11.4%) IB2 cervical cancers, according to 2018 FIGO stage. Hystological type were: 25 (56.8%) squamous carcinoma; 18 (40.9%) adenocarcinoma and 1 (2.3%) adenosquamous carcinoma. Pelvic lymphadenectomy was performed in 31 (70.4%) cases, while 13 (29.6%) patients had only sentinel node mapping. Four (9.1%) patients received neoadjuvant chemotherapy. In 7 (15.9%) patients conservative treatment was discontinued (5 nodal involvement, 2 no response to chemotherapy) and 2 (4.5%) patients asked for definitive treatment (hysterectomy) following a negative nodal evaluation. Among 35 (79.6%) patients who retained their childbearing potential: 17 (48.6%) had a second conization; 2 (5.7%) relapsed and underwent definitive treatment. After a median follow-up of 51 (range 1–184) months no deaths were reported. Twenty-two (66.7%) women attempted to conceive. There were 13 natural pregnancies among 12 (54.5%) women who got pregnant. Live birth rate was 76.9%: nine (69.2%) term and one (7.7%) preterm (at 32w) deliveries. Two (15.4%) miscarriage (1st and 2nd trimester) and one (7.7%) termination of pregnancy for medical reasons were recorded. Conclusion: Conization plus laparoscopic nodal evaluation is an ultraconservative but feasible option in the setting of fertility-sparing treatment for early-stage cervical cancer patients. Disclosures: The authors declare that there are no conflicts of interest. No funding sources supported this investigation.